Method for manufacturing a laminate, and method for manufacturing synthetic leather

JP7939625B2Active Publication Date: 2026-10-22DIC CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2025563408
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-12-12
Filing Date
2024-11-28
Publication Date
2026-10-22
Estimated Expiration
2044-11-28

AI Technical Summary

Benefits of technology

【0011】 本発明によれば、即剥離性、柔らかい風合いを有しつつ、加工性が良好な積層体、及び、当該積層体を有する合成皮革を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007939625000001
    Figure 0007939625000001
  • Figure 0007939625000002
    Figure 0007939625000002
Patent Text Reader

Abstract

The present invention provides a method for producing a laminate comprising a base material (i) and a urethane foam layer (ii). The method comprises: a step for applying a urethane foam layer-forming material onto a release paper sheet to form the urethane foam layer (ii); a step for bonding the base material (i) onto the urethane foam layer (ii) by a wet lamination method; and a step for peeling off the release paper sheet. The method is characterized in that: the urethane foam layer (ii) is in direct contact with the base material (i); the urethane foam layer-forming material contains a urethane resin (A) having a nonionic group; and the flow initiation temperature of the urethane resin (A) is higher than 130°C. A laminate produced by this production method exhibits good workability while having immediate peelability and soft texture.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a laminate, and a method for producing synthetic leather.

Background Art

[0002] Urethane resins are widely used in the production of synthetic leather including artificial leather due to their good mechanical strength and favorable feel. For synthetic leather applications, solvent-based urethane resins containing N,N-dimethylformamide (DMF) have been the mainstream up to now. However, against the background of DMF regulations in Europe, tightened VOC emission regulations in China and Taiwan, and DMF regulations by major apparel manufacturers, there is a demand for eliminating DMF from the urethane resin compositions for each layer constituting synthetic leather. Among these, water-based urethane (PUD) in which a urethane resin is dispersed in water is being studied as an alternative raw material for the intermediate porous layer formed by wet coagulation of conventional solvent-based urethane resins.

[0003] For example, Patent Document 1 discloses a foam-forming composition characterized by containing (A) a first self-emulsifying aqueous polyurethane resin having at least one hydrophilic functional group selected from the group consisting of a sulfo group and a sulfonate group, (B) a second self-emulsifying aqueous polyurethane resin having at least one hydrophilic functional group selected from the group consisting of a carboxy group and a carboxylate group, (C) a crosslinking agent, (D) a foaming agent, (E) a thickener, and (F) water, and a leather material provided with a foamed resin layer made of a foamed cured product of the foam-forming composition.

[0004] However, in conventional synthetic leather as described in Patent Document 1, an adhesive layer is required between the base material and the urethane foam layer. For this reason, aging for a relatively long period of time has to be performed, which has a problem in productivity.

[0005] Furthermore, in recent years, there has been a demand for synthetic leather that is soft in texture while also exhibiting good processability, such as making the pattern of the embossed surface more clearly visible. However, there is currently no product that satisfies these increasingly stringent requirements and does not meet the demands of the market.

[0006] Therefore, there was a need for a laminate that possessed easy peelability, a soft texture, and good processability, as well as synthetic leather having said laminate. [Prior art documents] [Patent Documents]

[0007] [Patent Document 1] Japanese Patent Publication No. 2020-109152 [Overview of the project] [Problems that the invention aims to solve]

[0008] The present invention aims to provide a laminate that has excellent processability while being easily peelable and having a soft texture, and a synthetic leather having said laminate. [Means for solving the problem]

[0009] As a result of diligent research to solve the above problems, the present inventors have discovered that by using a urethane resin that exceeds a specific flow initiation temperature and has a specific structure, and by creating a configuration in which the substrate (i) and the urethane foam layer (ii) are in direct contact by a wet lamination method, it is possible to produce a laminate that has immediate peelability, a soft texture, and good processability, thus completing the present invention.

[0010] In other words, the present invention relates to a method for manufacturing a laminate comprising a base material (i) and a urethane foam layer (ii), comprising the steps of: coating a urethane foam layer forming material onto a release paper to form a urethane foam layer (ii); bonding the base material (i) onto the urethane foam layer (ii) by a wet lamination method; and peeling off the release paper, wherein the urethane foam layer (ii) is in direct contact with the base material (i), the urethane foam layer forming material contains a urethane resin (A) having nonionic groups, and the flow initiation temperature of the urethane resin (A) is greater than 130°C. [Effects of the Invention]

[0011] According to the present invention, it is possible to provide a laminate that has immediate peelability, a soft texture, and good processability, as well as a synthetic leather having said laminate. [Modes for carrying out the invention]

[0012] The present invention provides a method for manufacturing a laminate, comprising the steps of: applying a urethane foam layer forming material onto a release paper to form a urethane foam layer (ii); bonding the substrate (i) onto the urethane foam layer (ii) by a wet lamination method; and peeling off the release paper, characterized in that the urethane foam layer (ii) is in direct contact with the substrate (i). In other words, the laminate obtained by the manufacturing method of the present invention is characterized in that there is no adhesive layer between the substrate (i) and the urethane foam layer (ii).

[0013] <Base material (i)> As the base material (i), for example, fiber base materials such as nonwoven fabrics, woven fabrics, and knitted fabrics made from polyester fibers, polyethylene fibers, nylon fibers, acrylic fibers, polyurethane fibers, acetate fibers, rayon fibers, polylactic acid fibers, cotton, linen, silk, wool, fiberglass, carbon fibers, and blends thereof; a nonwoven fabric impregnated with a resin such as polyurethane resin; a nonwoven fabric further provided with a porous layer; and a resin base material such as thermoplastic urethane (TPU) can be used.

[0014] <Urethane foam layer (ii)> The dry density of the urethane foam layer (ii) is 200 to 1000 kg / m 3 is preferable. In the present invention, the dry density of the urethane foam layer (ii) refers to the value obtained by subtracting the weight of the 10 cm square base material (i) from the weight of the 10 cm square laminate, and dividing the resulting value by the thickness of the urethane foam layer (ii).

[0015] The dry density of the urethane foam layer (ii) can be controlled by the expansion ratio. The expansion ratio can be controlled by the type of urethane used, the stirring rotation speed and time during foaming, and the like.

[0016] The thickness of the urethane foam layer (ii) is, for example, 50 to 600 μm.

[0017] The urethane foam layer forming material contains a urethane resin (A) having a nonionic group (hereinafter sometimes referred to as "component (A)").

[0018] ≪Urethane resin (A) having nonionic group≫ Component (A) is a urethane resin having a nonionic group, and is a urethane resin that can be dispersed in water. Component (A) has superior hydrolysis resistance compared to other water-dispersible urethane resins (for example, anionic urethane resins). In addition, since it is not necessary to add a crosslinking agent, the processability is excellent.

[0019] The flow initiation temperature of component (A) is higher than 130°C, preferably 150°C or higher, and more preferably 160°C or higher. When the flow initiation temperature of component (A) is higher than 130°C, the peel strength is improved. Further, when the flow initiation temperature of component (A) is equal to or higher than the above preferred lower limit, the peel strength is further improved.

[0020] The upper limit of the flow initiation temperature of component (A) is not particularly limited, and is, for example, preferably 250°C or lower.

[0021] The flow initiation temperature of component (A) can be controlled, for example, by appropriately adjusting the length of the molecular chain of the urethane resin. Specifically, it can be controlled by the addition amount of the chain extender (a3) in the "chain extension step" described later.

[0022] The flow initiation temperature of component (A) can be controlled, for example, by the type of polyol (a2) which is a raw material of the urethane resin (A) described later, the usage amount of the chain extender (a2-1), and the type of polyisocyanate (a1).

[0023] Examples of the method for adjusting the flow initiation temperature of component (A) to a high level include using a polyol with high crystallinity such as polycarbonate polyol as the polyol (a2), increasing the usage amount of the chain extender (a2-1), and using a polyisocyanate with high crystallinity such as 4,4'-diphenylmethane diisocyanate or dicyclohexylmethane diisocyanate as the polyisocyanate (a1).

[0024] Further, examples of the method for adjusting the flow initiation temperature of component (A) to a low level include using a polyol with low crystallinity such as polyoxypropylene glycol as the polyol (a2), reducing the usage amount of the chain extender (a2-1), and using a polyisocyanate with low crystallinity such as toluene diisocyanate or isophorone diisocyanate as the polyisocyanate (a1).

[0025] In the present invention, the flow initiation temperature of component (A) is a value measured by applying the urethane resin composition to release paper (coating thickness 150 μm), drying the coated composition with a hot air dryer at 70°C for 4 minutes and then at 120°C for 2 minutes to obtain a dried product, and measuring the dried product using a flow tester "CFT-500A" manufactured by Shimadzu Corporation (using a die with a caliber of 1 mm and a length of 1 mm, under a load of 98 N, at a temperature rise rate of 3°C / min).

[0026] (A) Specifically, the components include urethane resin made from polyisocyanate (a1) and polyol (a2).

[0027] [Polyisocyanate (a1)] Examples of polyisocyanates (a1) include aromatic polyisocyanates such as phenylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, naphthalene diisocyanate, polymethylene polyphenyl polyisocyanate, and carbodiimide diphenylmethane polyisocyanate; and aliphatic or alicyclic polyisocyanates such as hexamethylene diisocyanate, lysine diisocyanate, cyclohexane diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, xylylene diisocyanate, tetramethylxylylene diisocyanate, dimer acid diisocyanate, and norbornene diisocyanate. These polyisocyanates can be used individually or in combination of two or more.

[0028] The proportion of polyisocyanate (a1) used is preferably 5 to 60% by mass, more preferably 10 to 55% by mass, and even more preferably 15 to 50% by mass, based on 100% by mass of the total of polyisocyanate (a1) and polyol (a2).

[0029] [Polyol (a2)] Examples of polyols (a2) include polyether polyols, polyester polyols, polyacrylic polyols, polycarbonate polyols, and polybutadiene polyols. These polyols can be used individually or in combination of two or more types.

[0030] The number-average molecular weight of polyol (a2) is preferably 500 to 100,000, and more preferably 800 to 10,000, from the viewpoint of the mechanical strength of the resulting film. In this invention, the number-average molecular weight of polyol (a2) is the value measured by gel permeation column chromatography (GPC).

[0031] Among the above, polyether polyol (a21), polycarbonate polyol (a22), and polyester polyol (a23) are preferred as polyol (a2).

[0032] • Polyether polyol (a21) Examples of polyether polyols (a21) include polyethylene glycol, polypropylene glycol, polyethylene glycol-polytetramethylene glycol (block or random), polytetramethylene ether glycol, and polyhexamethylene glycol. Among these, polytetramethylene ether glycol is preferred.

[0033] • Polycarbonate polyol (a22) Examples of commercially available polycarbonate polyols (a22) include "ETERNACOLL UH-100" (manufactured by Ube Industries, Ltd.).

[0034] • Polyester polyol (a23) Examples of polyester polyols (a23) include esterification reaction products of low molecular weight polyols and polycarboxylic acids; ring-opened polymers of cyclic ester compounds such as ε-caprolactone; and copolymer polyesters of the aforementioned esterification reaction products or ring-opened polymers. Among these, ring-opened polymers of cyclic ester compounds such as ε-caprolactone are preferred.

[0035] Regarding the proportion of polyol (a2) used, in order to obtain even better mechanical strength, 40 to 95% by mass is preferred, 45 to 90% by mass is preferred, and 50 to 85% by mass is preferred, based on 100% by mass of the total of polyisocyanate (a1) and polyol (a2).

[0036] (A) The component may be a urethane resin made from polyisocyanate (a1), polyol (a2), chain extender (a3), and a compound having an oxyethylene structure (a4) (excluding compounds corresponding to (a1) to (a3) ​​above).

[0037] [Chain elongators (a3)] As the chain extender (a3), compounds with a molecular weight of less than 500 (preferably in the range of 50 to 450) can be used. Specifically, these include ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, hexamethylene glycol, saccharose, methylene glycol, glycerin, sorbitol, bisphenol A, 4,4'-dihydroxydiphenyl, 4,4'-dihydroxydiphenyl ether, and trimethylol. Examples of chain elongators include those having hydroxyl groups such as propane; and those having amino groups (-NH2, -NH-, -N(-)-) such as ethylenediamine, 1,2-propanediamine, 1,6-hexamethylenediamine, piperazine, 2,5-dimethylpiperazine, isophoronediamine, 1,2-cyclohexanediamine, 1,3-cyclohexanediamine, 1,4-cyclohexanediamine, 4,4'-dicyclohexylmethanediamine, 3,3'-dimethyl-4,4'-dicyclohexylmethanediamine, 1,4-cyclohexanediamine, and hydrazine. These chain elongators can be used alone or in combination of two or more. In this invention, the molecular weight of the chain elongator (a3) ​​is the value calculated from its chemical formula.

[0038] As the chain extender (a3), an amino group-containing chain extender (hereinafter also referred to as "amine-based chain extender") is preferred because it can easily extend the chain even at relatively low temperatures of 30°C or below, suppresses energy consumption during the reaction, provides even better texture and peel strength through the introduction of urea groups, and facilitates the high solid differentiation of component (A). More preferably, an amine-based chain extender with a molecular weight in the range of 30 to 250 is used. When two or more types of chain extenders (a3) ​​are used in combination, the average value of the molecular weight of each chain extender (a3) ​​is shown, and it is sufficient that this average value falls within the preferred molecular weight range.

[0039] The preferred ratio of the chain extender (a3) ​​is 0.1 to 30% by mass, and more preferably 0.5 to 10% by mass, of the total mass of the raw materials constituting component (A), in order to obtain an even better texture and peel strength, and to facilitate the high solid differentiation of component (A).

[0040] [Compounds having an oxyethylene structure (a4)] As the compound having an oxyethylene structure (a4), for example, polyether polyols having an oxyethylene structure such as polyethylene glycol, polyoxyethylene polyoxypropylene glycol, polyoxyethylene polyoxytetramethylene glycol, and polyethylene glycol dimethyl ether can be used. These compounds can be used individually or in combination of two or more. Among these, polyethylene glycol and / or polyethylene glycol dimethyl ether are preferred because they allow for easier control of hydrophilicity.

[0041] As for the proportion of compound (a4) having an oxyethylene structure, it is preferable that the amount used is 0.1 to 10% by mass, more preferably 0.2 to 10% by mass, and even more preferably 0.25 to 8% by mass, based on the total mass of the raw materials constituting component (A), in order to obtain even better mechanical strength.

[0042] (A) Component (A) can be used alone or in combination of two or more components.

[0043] The content of component (A) is preferably 60 to 99% by mass, more preferably 65 to 98% by mass, and even more preferably 68 to 97% by mass, relative to the total amount of solids constituting the urethane foam layer (ii).

[0044] [Method for producing urethane resin (A) having nonionic groups] (A) There are no particular limitations on the method for producing component (A), but one example is a method comprising the steps of: reacting a polyisocyanate (a1), a polyol (a2), and a compound having an oxyethylene structure (a4) in the absence of a solvent to obtain a urethane prepolymer (i) having an isocyanate group (hereinafter also referred to as the "prepolymer step"), then dispersing the urethane prepolymer (i) in water (hereinafter also referred to as the "emulsification step"), and then reacting the urethane prepolymer (i) dispersed in water with a chain extender (a3) ​​to obtain a urethane resin (A) having a nonionic group (hereinafter also referred to as the "chain extension step").

[0045] "Prepolymer process" The prepolymerization process is preferably carried out under solvent-free conditions. In conventional technology, the prepolymerization process was generally carried out in organic solvents such as methyl ethyl ketone and acetone. However, a solvent removal process was required after the emulsification process to remove the organic solvent, which took several days in actual production settings. Furthermore, it was difficult to completely remove the organic solvent in the solvent removal process, and in many cases, some organic solvent remained, making it difficult to fully meet environmental requirements. On the other hand, by manufacturing the prepolymer under solvent-free conditions, a urethane resin that is completely free of organic solvents can be obtained, and the production process can also be streamlined.

[0046] In the prepolymerization process, the molar ratio [isocyanate groups / (hydroxyl groups and amino groups)] between the total number of hydroxyl groups in the polyol (a2) and the compound having an oxyethylene structure (a4) and the isocyanate groups in the polyisocyanate (a1) is preferably in the range of 1.1 to 3, and more preferably in the range of 1.2 to 2, from the viewpoint of obtaining an even better texture and peel strength.

[0047] The reaction in the prepolymerization step may be carried out, for example, at 50 to 120°C for 1 to 10 hours.

[0048] "Emulsification process" The emulsification process can be carried out using, for example, a reaction vessel equipped with stirring blades; kneaders such as kneaders, continuous kneaders, tapered rolls, single-screw extruders, twin-screw extruders, tri-screw extruders, universal mixers, plastmills, and bodeta-type kneaders; rotary dispersion mixers such as homomixers, static mixers, filmix, Ebara Milder, Creamix, Ultra Turlux, Cavitron, and Biomixer; ultrasonic dispersion devices; and devices without moving parts that can mix by the flow of the fluid itself, such as in-line mixers.

[0049] In the emulsification process, ion-exchanged water, distilled water, etc., can be used as the water. These types of water can be used individually or in combination of two or more.

[0050] The emulsification process is preferably carried out at a temperature at which water does not evaporate, for example, in the range of 10 to 90°C. The emulsification process can be carried out using the same equipment as the prepolymerization process.

[0051] "Chain extension process" The chain extension step is a process in which the isocyanate groups present in the urethane prepolymer (i) react with the chain extension agent (a3) ​​to increase the molecular weight of the urethane prepolymer (i) and obtain component (A). From the viewpoint of productivity, it is preferable to carry out the chain extension step at a temperature of 50°C or lower.

[0052] In the chain extension process, the molar ratio [(hydroxyl groups and amino groups) / isocyanate groups] of the isocyanate groups of the urethane prepolymer (i) to the total of the hydroxyl groups and amino groups of the chain extender (a3) ​​is preferably in the range of 0.8 to 1.1, and more preferably in the range of 0.9 to 1, in order to obtain even better texture and peel strength.

[0053] ≪Optional ingredients≫ The polyurethane foam layer (ii) may contain any components other than component (A).

[0054] Examples of the optional components include surfactants, thickeners, leveling agents, pigments, defoamers, crosslinking agents, emulsifiers, neutralizing agents, film-forming aids, urethane catalysts, fillers, dyes, flame retardants, and antiblocking agents. These optional components can be used individually or in combination of two or more.

[0055] Furthermore, while it is preferable that component (A) is substantially free of organic solvents when manufacturing it, organic solvents may be added as additives.

[0056] Furthermore, it is preferable that the urethane foam layer (ii) does not contain a crosslinking agent.

[0057] Furthermore, the urethane foam layer (ii) preferably contains component (A), a surfactant, and a thickener.

[0058] [Surfactants] As a surfactant, a surfactant having a hydrophobic portion with 10 or more carbon atoms is preferred.

[0059] Specifically, as surfactants, long-chain carboxylates are preferred, long-chain carboxylates having 10 to 20 carbon atoms are preferred, and long-chain carboxylates having 14 to 20 carbon atoms are more preferred.

[0060] Examples of surfactants include long-chain alkali metal carboxylates, long-chain amine carboxylates, and long-chain ammonium carboxylates.

[0061] Sodium and potassium are preferred alkali metals used as raw materials for long-chain alkali metal carboxylates.

[0062] Examples of amines used as raw materials for long-chain carboxylic acid amine salts include monoamines, alkanolamines, and polyamines.

[0063] Examples of monoamines include primary, secondary, and tertiary monoamines.

[0064] Examples of primary amines include ethylamine, n-propylamine, butylamine, 1-ethylbutylamine, 1,3-diaminopropane, and cyclohexylamine.

[0065] Examples of secondary amines include diethylamine, di-n-propylamine, di-n-butylamine, 4,4'-diaminodiphenylamine, diethylenetriamine, tetraethylenepentamine, N-(2-aminoethyl)ethanolamine, and morpholine.

[0066] Examples of tertiary amines include dimethylethylamine, diethylmethylamine, triethylamine, and tributylamine.

[0067] Examples of alkanolamines include monoethanolamine, diethanolamine, triethanolamine, diethylethanolamine, and propanolamine.

[0068] Examples of polyamines include alkylene polyamines such as ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, propylenediamine, dipropylenetriamine, tripylenetetramine, tetrapropylenepentamine, pentapropylenehexamine, butylenediamine, dibutylentriamine, tripbutylenetetramine, tetrabutylenepentamine, and pentabutylenehexamine; N-alkylethylenediamines such as N-methylethylenediamine, N-ethylethylenediamine, and N-propylethylenediamine; N-alkenylethylenediamines such as N-vinylethylenediamine, N-propenylethylenediamine, and N-butenylethylenediamine; and N-alkyl or N-alkenylalkylene polyamines such as N-alkyldiethylenetriamine, N-alkenyldiethylenetriamine, and N-alkyltriethylenetetramine.

[0069] As for the surfactant, among the above, long-chain ammonium carboxylates having 10 to 20 carbon atoms are preferred, long-chain ammonium carboxylates having 14 to 20 carbon atoms are more preferred, and ammonium stearate is even more preferred.

[0070] Surfactants can be used individually or in combination of two or more types.

[0071] The surfactant content is preferably 0.01 to 30% by mass, more preferably 0.1 to 20% by mass, and even more preferably 1 to 10% by mass, based on the total amount of solids constituting the urethane foam layer (ii).

[0072] [Thickener] Examples of thickening agents include cellulose thickeners; acrylic thickeners; urethane thickeners; protein thickeners such as casein, sodium caseate, and ammonium caseate; polyvinyl thickeners such as polyvinyl alcohol, polyvinylpyrrolidone, and polyvinyl benzyl ether copolymers; polyether thickeners such as Pluronic® polyether, polyether dialkyl esters, polyether dialkyl ethers, and polyether epoxy modified products; maleic anhydride thickeners such as vinyl methyl ether-maleic anhydride copolymers; and polyamide thickeners such as polyamideamine salts.

[0073] Thickening agents can be used alone or in combination of two or more types.

[0074] The amount of the thickening agent is preferably 0.01 to 10% by mass, more preferably 0.05 to 8% by mass, and even more preferably 0.1 to 5% by mass, relative to the total amount of solids constituting the urethane foam layer (ii).

[0075] <Other layers> The laminate obtained by the manufacturing method of the present invention may include other layers besides the base material (i) and the urethane foam layer (ii). Examples of other layers include a skin layer (iii).

[0076] ≪Epidermal layer≫ The epidermal layer (iii) can be formed using known materials and by known methods.

[0077] The epidermal layer (iii) contains, for example, solvent-based urethane resin, water-based urethane resin, silicone resin, polypropylene resin, polyester resin, etc.

[0078] Among the above, the epidermal layer (iii) preferably contains a urethane resin (A) having nonionic groups, and more preferably contains the same urethane resin as the urethane foam layer (ii) described above.

[0079] A surface treatment layer (iv) may be further provided on the epidermal layer (iii) as needed, for purposes such as improving scratch resistance or imparting gloss. Examples of materials for forming the surface treatment layer (iv) include known water-based urethane resins, solvent-based urethane resins, solvent-free urethane resins, water-based acrylic resins, silicone resins, polypropylene resins, polyester resins, and vinyl chloride resins. These materials can be used individually or in combination of two or more.

[0080] (Method of manufacturing a laminate) The method for manufacturing the laminate of the present invention is not particularly limited as long as it includes the steps of: (X) applying a urethane foam layer forming material onto a release paper to form a urethane foam layer (ii); (Y) bonding the substrate (i) onto the urethane foam layer (ii) by a wet lamination method; and (Z) peeling off the release paper. However, it is preferable to carry out the steps in the order of (X), (Y), and (Z).

[0081] The method for forming the urethane foam layer (ii) in step (X) is not particularly limited, but examples include a method in which a urethane foam layer forming material is foamed to obtain a foaming liquid, this foaming liquid is applied to a release paper and dried.

[0082] Methods for foaming the aforementioned urethane foam layer forming material to obtain a foaming liquid include, for example, manual stirring and mechanical foaming using a mixer such as a mechanical mixer. Among these, the method using a mixer is preferred because it allows for easy acquisition of a foaming liquid. When using a mixer, for example, a method of stirring at 500 to 3,000 rpm for 10 seconds to 10 minutes is suggested. In this case, it is preferable to increase the volume by 1.2 to 7 times, and more preferably by 1.3 to 2 times, before and after foaming, in order to obtain a urethane foam layer (ii) with a good texture.

[0083] In step (Y), a wet lamination method is used to bond the urethane foam layer (ii) and the substrate (i). In this invention, the wet lamination method refers to a method in which a urethane foam layer forming material is applied to a mold-release treated substrate and bonded before it is completely cured.

[0084] (synthetic leather) The laminate obtained by the manufacturing method of the present invention described above has excellent peelability, a soft texture, and good processability, making it particularly suitable for use as synthetic leather. [Examples]

[0085] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to the following examples.

[0086] [Synthesis of urethane resin] <Synthesis of urethane resin (AX-1)> In the presence of 0.1 parts by mass of stannous octylate, 1,000 parts by mass of polyether polyol (Mitsubishi Chemical Corporation's "PTMG2000", number average molecular weight: 2,000), 38 parts by mass of polyethylene glycol (NOF Corporation's "PEG600", number average molecular weight: 600), and 262 parts by mass of dicyclohexylmethane diisocyanate were reacted at 100°C until the NCO% reached 2.8% by mass to obtain urethane prepolymer A1. To 1,000 parts by mass of urethane prepolymer A1 heated to 70°C, 200 parts by mass of a 20% by mass aqueous solution of sodium dodecylbenzenesulfonate ("Neogen S-20F" manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) and 467 parts by mass of water were mixed to obtain an emulsion. Subsequently, a diluted aqueous solution of piperazine containing amino groups equivalent to 95% of the NCO groups was immediately added to extend the chain, and finally an aqueous dispersion of urethane resin (AX-1) with a non-volatile content of 55% by mass was obtained. Next, an aqueous dispersion of urethane resin (AX-1) was applied to release paper (coating thickness 150 μm), and dried in a hot air dryer at 70°C for 4 minutes, then at 120°C for 2 minutes to obtain a dried product. The flow initiation temperature of this dried product was measured using a Shimadzu Corporation flow tester "CFT-500A" (using a die with a diameter of 1 mm and a length of 1 mm, a load of 98 N, and a heating rate of 3°C / min), and the flow initiation temperature of the urethane resin (AX-1) was found to be 180°C.

[0087] <Synthesis of urethane resin (AX-2)> In the presence of 0.1 parts by mass of stannous octylate, 1,000 parts by mass of polycarbonate polyol (ETERNACOLL UH-100, manufactured by Ube Industries, Ltd., number average molecular weight: 1,000), 75 parts by mass of polyethylene glycol (PEG600, manufactured by NOF Corporation, number average molecular weight: 600), and 525 parts by mass of dicyclohexylmethane diisocyanate were reacted at 100°C until the NCO% reached 4.6% by mass to obtain urethane prepolymer A2. To 1,000 parts by mass of urethane prepolymer A2 heated to 70°C, 200 parts by mass of a 20% by mass aqueous solution of sodium dodecylbenzenesulfonate ("Neogen S-20F" manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) and 325 parts by mass of water were mixed to obtain an emulsion. Subsequently, an aqueous dilution of piperazine containing amino groups equivalent to 95% of the NCO groups was immediately added to extend the chain, and finally an aqueous dispersion of urethane resin (AX-2) with a non-volatile content of 55% by mass was obtained. The flow initiation temperature of the urethane resin (AX-2), measured using the same method as described above, was 175°C.

[0088] <Synthesis of urethane resin (AX-3)> An aqueous dispersion of urethane resin (AX-3) was obtained by the same method as described in <Synthesis of Urethane Resin (AX-2)> above, except that the polyether polyol was replaced with a polyester polyol (Daicel Corporation's "Praxel 210", number average molecular weight: 1,000). The flow initiation temperature of the urethane resin (AX-3), measured using the same method as described above, was 160°C.

[0089] <Synthesis of urethane resin (X-4)> In the presence of 0.1 parts by mass of stannous octylate, 1,000 parts by mass of polyether polyol (Mitsubishi Chemical Corporation's "PTMG2000", number average molecular weight: 2,000), 38 parts by mass of polyethylene glycol (NOF Corporation's "PEG600", number average molecular weight: 600), and 262 parts by mass of dicyclohexylmethane diisocyanate were reacted at 100°C until the NCO% reached 2.8% by mass to obtain urethane prepolymer A1. To 1,000 parts by mass of urethane prepolymer A1 heated to 70°C, 200 parts by mass of a 20% by mass aqueous solution of sodium dodecylbenzenesulfonate ("Neogen S-20F" manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) and 467 parts by mass of water were mixed to obtain an emulsion. Subsequently, a diluted aqueous solution of piperazine containing amino groups equivalent to 75% of the NCO groups was immediately added to extend the chain, and finally, an aqueous dispersion of urethane resin (X-4) with a non-volatile content of 55% by mass was obtained. The flow initiation temperature of the urethane resin (X-4), measured using the same method as described above, was 130°C.

[0090] <Preparation of urethane resin (X-5)> As the urethane resin (X-5), we prepared the ether-based PUD "Hydran WLS-120AR" (manufactured by DIC Corporation). The flow initiation temperature of the urethane resin (X-5), measured using the same method as described above, was 160°C.

[0091] <Synthesis of urethane resin (X-6) for adhesive layer> In the presence of 1,225 parts by mass of methyl ethyl ketone and 0.1 parts by mass of stannous octylate, 1,000 parts by mass of polyether polyol (Mitsubishi Chemical Corporation, "PTMG1000", number average molecular weight: 1,000), 50 parts by mass of 2,2'-dimethylolpropionic acid, and 175 parts by mass of isophorone diisocyanate were reacted at 70°C until the solution viscosity reached 20,000 mPa·s. Then, 3 parts by mass of methanol were added to stop the reaction and obtain a methyl ethyl ketone solution of anionic urethane resin. 61 parts by mass of polyoxyethylene distyrenated phenyl ether and 38 parts by mass of triethylamine were mixed with this urethane resin solution, and then 2,450 parts by mass of ion-exchanged water was added to perform phase inversion emulsification to obtain an emulsion in which the urethane resin was dispersed in water. Next, the methyl ethyl ketone was distilled off from the emulsion to obtain an aqueous dispersion of urethane resin (X-6) with a non-volatile content of 50% by mass.

[0092] [Method for manufacturing laminates] <Laminate of Example 1 (1)> • Preparation of foam layer composition (X1) A foaming layer composition (X1) was prepared by stirring 100g of an aqueous dispersion of urethane resin (AX-1), 2.0g of a thickener (Borch Gel ALA; manufactured by Borchers), and 3.0g of a surfactant (ammonium stearate) in a mechanical mixer at 2400 rpm, incorporating air to achieve a volume of 150% of the initial volume.

[0093] • Preparation of the laminate (1) of Example 1 A foam layer was formed by coating a release paper (EK-100D; manufactured by Lintech) with a knife coater (coating thickness 600 μm) using a foam layer composition (X1). Next, a substrate (thermoplastic urethane (TPU)) was pressed onto the foam layer to bond it to the substrate. After that, the laminate (1) (synthetic leather) of Example 1 was obtained by drying at 120°C for 4 minutes. The dry density of the urethane foam layer in this laminate (1) was 630 kg / m³. 3In this invention, the dry density of the urethane foam layer is the value obtained by subtracting the weight of the base material per 10 cm square from the weight of the laminate of Example 1 per 10 cm square, and dividing this value by the thickness of the urethane foam layer (the same applies hereinafter).

[0094] <Laminate of Example 2 (2)> Laminate (2) of Example 2 was manufactured using the same manufacturing method as <Laminate of Example 1>, except that the aqueous dispersion of urethane resin (AX-1) in the foam layer composition (X1) was changed to an aqueous dispersion of urethane resin (AX-2). The dry density of the urethane foam layer in this laminate (2) was 520 kg / m³. 3 That was the case.

[0095] <Laminate of Example 3 (3)> Laminate (3) of Example 3 was manufactured using the same manufacturing method as <Laminate of Example 1>, except that the aqueous dispersion of urethane resin (AX-1) in the foam layer composition (X1) was changed to an aqueous dispersion of urethane resin (AX-3). The dry density of the urethane foam layer in this laminate (3) was 780 kg / m³. 3 That was the case.

[0096] <Laminate of Comparative Example 1 (R1)> A laminate (R1) of Comparative Example 1 was manufactured using the same manufacturing method as the laminate of Example 1, except that the aqueous dispersion of urethane resin (AX-1) in the foam layer composition (X1) was replaced with an aqueous dispersion of urethane resin (X-4). The dry density of the urethane foam layer in this laminate (R1) was 600 kg / m³. 3 That was the case.

[0097] <Laminate of Comparative Example 2 (R2)> A laminate (R2) of Comparative Example 2 was manufactured using the same manufacturing method as for the laminate of Example 1, except that the aqueous dispersion of urethane resin (AX-1) in the foam layer composition (X1) was changed to an aqueous dispersion of urethane resin (X-5), and 4.0 g of a crosslinking agent (Carbodilite SV-02; manufactured by Nisshinbo Chemical Co., Ltd.) was added.

[0098] <Laminate of Comparative Example 3 (R3)> The laminate (R3) of Comparative Example 3 was manufactured using the same manufacturing method as the laminate of Example 1, except that the aqueous dispersion of urethane resin (AX-1) in the foam layer composition (X1) was changed to an aqueous dispersion of urethane resin (X-5).

[0099] <Laminate of Comparative Example 4 (R4)> • Preparation of adhesive layer compositions 100 g of an aqueous dispersion of urethane resin (X-6), 0.1 g of an antifoaming agent (Tego Foamex 800; manufactured by Evonik), and 1.0 g of a thickening agent (Borch Gel 0620; manufactured by Borchers) were mixed in a mechanical mixer at 2000 rpm for 2 minutes, and then degassed using a vacuum degasser to prepare the adhesive layer composition (X-6).

[0100] • Fabrication of the laminate (R4) of Comparative Example 4 A foam layer composition (X1) was applied to a release paper (EK-100D; manufactured by Lintech) using a knife coater (coating thickness 600 μm) to form a foam layer (drying conditions 70°C for 2 min, 120°C for 2 min). Next, an adhesive layer composition (X-6) was applied to the foam layer using a knife coater (coating thickness adjusted so that the coating thickness would be 50 μm when dry), and an adhesive layer was formed using a hot air dryer (drying conditions 90°C for 3 minutes). A substrate (thermoplastic urethane (TPU)) was placed on the adhesive layer and laminated using a laminator at a temperature of 100°C, a pressure of 7.5 MPa, and a feed rate of 0.5 m / min to obtain the laminate (R4) of Comparative Example 4.

[0101] <Laminate of Comparative Example 5 (R5)> A foam layer composition (X1) was applied to a release paper (EK-100D; manufactured by Lintech) using a knife coater (coating thickness 600 μm) to form a foam layer (drying conditions 70°C × 2 min, 120°C × 2 min). Next, an adhesive layer composition (X-6) was applied onto the foam layer using a knife coater (coating thickness adjusted so that the coating thickness would be 50 μm after drying), a substrate (thermoplastic urethane (TPU)) was placed on the adhesive layer, and the layers were bonded using a laminator at a temperature of 25°C, a pressure of 5 MPa, and a feed rate of 0.5 m / min. The adhesive layer was then dried in a hot air dryer (drying conditions 120°C × 2 min) to obtain the laminate (R5) of Comparative Example 5.

[0102] The laminates obtained in the above examples and comparative examples were used for the following evaluations.

[0103] [Evaluation of peel strength] A 2.5 cm wide hot melt tape (BW-2, manufactured by Sun Chemical Co., Ltd.) was placed on the surface of the laminate and heated and pressed at 150°C for 30 seconds to adhere the tape. The laminate was cut along the width of the hot melt tape. The substrate and the hot melt tape were clamped in a chuck, and the substrate and foam layer of the cut laminate were peeled off. The peel strength was measured using an Autograph (manufactured by Shimadzu Corporation). The average value of the obtained data was calculated, converted to a 1 cm width, and the peel strength was evaluated according to the following criteria. The results are shown in Tables 1 and 2.

[0104] A:3kgf / cm or more B: 1.5 or higher ~ less than 3 kgf / cm² C: Less than 1.5 kgf / cm²

[0105] [Evaluation of immediate peelability] The peel strength of each laminate was measured immediately after manufacturing and after aging (heating at 60°C for several weeks), and the immediate peelability was evaluated according to the following criteria. The results are shown in Tables 1 and 2.

[0106] A: The difference in peel strength is less than 0.5 kgf / cm. B: The difference in peel strength is 0.5 kgf / cm or more.

[0107] [Evaluation of hydrolysis properties] Each laminate was left standing for 3 weeks under moist heat conditions of 70°C and 95%RH, and its hydrolysis properties were evaluated according to the following criteria. The results are shown in Tables 1 and 2.

[0108] A: There are no abnormalities in the appearance. B: The appearance has changed in gloss, and / or the texture is sticky.

[0109] [Evaluation of processability] Embossing was applied to each example of the laminate. Next, the appearance of each example's laminate was compared, and the clarity of the transferred pattern was observed using a scanning electron microscope (SEM), and the processability was evaluated according to the following criteria. The results are shown in Tables 1 and 2.

[0110] A: The embossed pattern is clearly captured, and SEM observation confirms that the pattern is sharp. B: The embossed pattern is not clearly captured, and SEM observation confirms that the pattern is not sharp.

[0111] [Evaluation of texture] The texture of each laminate was evaluated by touch.

[0112] A: It is flexible and soft. B: It lacks flexibility and is stiff.

[0113] [Table 1]

[0114] [Table 2]

[0115] As shown in Tables 1 and 2, the laminates of the examples showed better peel strength, immediate peelability, hydrolysis resistance, processability, and texture compared to the laminates of the comparative examples. Therefore, it was confirmed that the laminate of the example has good processability while possessing immediate peelability and a soft texture.

Claims

1. A method for manufacturing a laminate comprising a base material (i) and a urethane foam layer (ii), A step of applying a urethane foam layer forming material onto a release paper to form a urethane foam layer (ii), A step of bonding the substrate (i) onto the urethane foam layer (ii) by a wet lamination method, The process includes the step of peeling off the aforementioned release paper, The urethane foam layer (ii) is in direct contact with the substrate (i), The urethane foam layer forming material contains a urethane resin (A) having nonionic groups, The flow initiation temperature of the urethane resin (A) is above 130°C. The urethane resin (A) is made from polyisocyanate (a1), one or more polyols (a2) selected from the group consisting of polyether polyols, polycarbonate polyols, and polyester polyols, and a compound (a4) having an oxyethylene structure as essential raw materials. The proportion of the compound (a4) having the oxyethylene structure used is in the range of 0.1 to 10% by mass of the total mass of the raw materials constituting the urethane resin (A). A method for producing a laminate, characterized in that the urethane resin (A) is obtained through a prepolymerization step in which the polyisocyanate (a1), the polyol (a2), and the compound having an oxyethylene structure (a4) are reacted in the absence of a solvent to obtain a urethane prepolymer (i) having an isocyanate group.

2. The method for manufacturing a laminate according to claim 1, wherein the flow initiation temperature of the urethane resin (A) is 150°C or higher.

3. The method for producing a laminate according to claim 1, wherein the urethane foam layer (ii) further contains a surfactant.

4. The method for producing a laminate according to claim 3, wherein the surfactant is a long-chain carboxylate.

5. The dry density of the aforementioned urethane foam layer (ii) is 200 to 1000 kg / m³ 3 The method for manufacturing a laminate according to claim 1.

6. A method for producing synthetic leather, characterized by having a laminate obtained by the manufacturing method described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Aqueous urethane resin composition for forming porous layer

    JP2000297211A

  • Method for producing porous structure

    JP2002194679A

  • Nubuck-toned sheet-like article and method for producing the same

    JP2010031443A

  • Composition for forming foam body, foam body, manufacturing method of foam body, and leather material

    JP2020109152A

  • Synthetic leather

    JP2022013701A